Auriculotemporal nerve syndrome (Frey's syndrome): A literature review and case report - Roy Petel (Wolters Kluwer Medknow Publications, 2019)
Frey's syndrome in children is rare and often erroneously attributed to food allergy. A description of a case of Frey's syndrome in a child and a review of the literature is provided. Awareness of this condition is important for the pediatric dentist to avoid unnecessary medical procedures and provide reassurance to the dental team in the setting of this benign condition.